The The Effect of Transformational Leadership Style on Organizational Citizenship Behavior Through Leader-Member Exchange as a Mediator Variable and Dependence on the Leader as a Moderator Variable in Music Performances : A Study on Student Project Performing Art and Sport Management Ciputra University - Abdi Cahya, Kristian Sena; Kurniawan, Daniel (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
This study investigates six key relationships in the context of music performances: (1) the impact of transformational leadership style on leader-member exchange (LMX), (2) the impact of transformational leadership on organizational citizenship behavior (OCB), (3) the influence of LMX on OCB, (4) the mediating role of LMX in the relationship between transformational leadership and OCB, (5) the moderating effect of dependence on the leader in the relationship between transformational leadership and OCB, and (6) the moderating effect of dependence on the leader in the relationship between LMX and OCB. The population comprises 127 committee members from the virtual music concert One Voice for All, the musical drama Merpati Putih, and UC Summerfest 2022 (International Business Management Program, Faculty of Management and Business, Ciputra University). Data were collected through validated and reliable questionnaires and analyzed using SEM-PLS, including path coefficients, indirect effects, and F-square moderation tests. The findings show: (1) transformational leadership significantly and positively affects LMX, (2) transformational leadership significantly and positively affects OCB, (3) LMX significantly and positively affects OCB, (4) LMX significantly mediates the effect of transformational leadership on OCB, (5) dependence on the leader weakens and does not significantly moderate the effect of transformational leadership on OCB, and (6) dependence on the leader strengthens but does not significantly moderate the effect of LMX on OCB.